Bank Rating Changes and Bank Stock Returns-Puzzling Evidence from the Emerging Markets - Richards, Anthony; Deddouche, David (Washington, D.C. : International Monetary Fund, 1999)
This paper examines the performance of emerging market bank stocks around the time of rating changes by major international agencies. The data suggest that downgrades on average have followed periods of negative cumulative abnormal returns for banks, although upgrades have not followed periods of positive returns. More important, stock prices either do not respond to rating changes or respond in the opposite direction to what would be expected if announcements conveyed value-relevant information. The paper concludes that there are limits to the extent that supervisors in emerging markets can rely on market participants to monitor the safety and soundness of banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet